2021
DOI: 10.1002/mar.21534
|View full text |Cite
|
Sign up to set email alerts
|

How aesthetic features convey the concept of brand premiumness

Abstract: When do aesthetic properties convey the concept of premiumness? Is symmetry tied to the perception of premiumness due to symmetry's evolutionary association to quality, an association not present with other aesthetic features like curvature? Usually, symmetry and curvature are preferred features. However, preference itself may not suffice to evoke premiumness. With this in mind, we predicted that symmetry (vs. asymmetry) and high(vs. low) product quality would both increase the perception of premiumness of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…Past studies provide evidence of how CC impacts consumers': (1) brand responses (Hernandez et al, 2019) and (2) price judgements (Berdysheva & Romanova, 2017). As a result, premium brand marketers (Pombo & Velasco, 2021) must understand how to mitigate the negative impact of CC on BL and WPP, and our research makes an endeavor to contribute to this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies provide evidence of how CC impacts consumers': (1) brand responses (Hernandez et al, 2019) and (2) price judgements (Berdysheva & Romanova, 2017). As a result, premium brand marketers (Pombo & Velasco, 2021) must understand how to mitigate the negative impact of CC on BL and WPP, and our research makes an endeavor to contribute to this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…While round typefaces are conventionally perceived to be soft and feminine, angular typefaces are perceived to be hard and masculine (Grohmann, 2016; Wang et al, 2020). In addition, round (vs. angular) typefaces generally induce feelings of pleasantness and friendliness (Henderson et al, 2004; Pombo & Velasco, 2021). Furthermore, a separate line of crossmodal research has shown that round typefaces tend to be associated with a sweet taste, whereas angular typefaces tend to be matched with bitter, sour, and salty tastes instead (Velasco et al, 2014; Velasco, Hyndman, et al, 2018; Velasco & Spence, 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The results show that perceived naturalness is linked to (1) the way food has been grown, ( 2) what ingredients and technologies have been used to manufacture a product, and (3) the product properties (e.g., freshness, flavor, accordance with nature, and healthiness). What is relevant to our theoretical framework is that these dimensions are the ones that influence consumer preferences and product perception (Pombo & Velasco, 2021;Shao & Li, 2021;Zhou et al, 2021). Rozin (2005) and Rozin et al (2004) suggest that perceived naturalness can be elicited via two marketing techniques.…”
Section: Perceived Naturalnessmentioning
confidence: 99%